Adverse Effects of Tetanus Toxoid, Reduced Diphtheria Toxoid, and Acellular Pertussis Vaccine in 6- to 7-Year-Old Children - Sung-Hsi Wei; Yen-Nan Chao; Song-En Huang; Tsuey-Feng Lee; Luan-Yin Chang (Pediatrics and Neonatology, 2011)
Although the safety profile of tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccines in adolescents and adults has been documented, few data have reported about their adverse events in children. Healthy 6- to 7-year-old children who were immunized with Tdap vaccine were evaluated for adverse events on Days 1, 2, 4, and 7 postimmunization. Information of sex, body mass index (BMI), and previous diphtheria-pertussis-tetanus (DPT) immunization history was obtained and evaluated for the association with the adverse events. A total of 243 6- to 7-year-old children were immunized with Tdap. Among the 243 children immunized, remarkable adverse events included redness more than or equal to 10 mm in 47 (19%) children, induration more than or equal to 10 mm in 57 (23%), tenderness in 130 (53%), and fever in 12 (5%). Redness and induration resolved in 7 days and fever resolved on Day 4. The adverse events were not associated with gender, BMI above the mean value, or the type of fourth DPT immunization. Adverse events after Tdap vaccination were mild and dissolved within 7 days in 6- to 7-year-old children.